Perancangan UI/UX pada Website Toko Kue Jager Bakery dengan Metode Design Thinking - Muhammad Rizky Wahyudi; Nur Widjiyati (Jurnal Teknologi Informasi dan Multimedia, 2025)
A patisserie website is a key channel for interacting with consumers and has great potential to increase market reach. Jäger Bakery comes as a new innovation in the world of online cake shops designed to provide a better user experience compared to other cake shop websites. The main problems found on cake shop websites are suboptimal design, such as unattractive appearance, confusing navigation, and mismatch between user needs and features provided. This has the potential to reduce user comfort and affect the level of customer satisfaction. Therefore, the purpose of this research is to identify and design a design solution that better suits user preferences and improves the quality of the online shopping experience at the cake shop. The Design Thinking method was chosen for its approach that focuses on deeply understanding user needs and wants, and generating innovative and effective design solutions. The research process begins with the Empathize stage to gather information from users, followed by Define to formulate the main problem, then continues to the Ideate, Prototype, and finally Test stages to test the design that has been made. Usability testing results showed an increase in Direct Success Rate (DSR) from 65% to 93.8% and a decrease in Missclick Rate from 54.2% to 8%. In addition,System Usability Scale (SUS) testing resulted in a Maze Usability Score (MAUS) of 79.23, which is categorized as “good”. These results prove that the application of the Design Thinking method has successfully improved the UI/UX of the Jäger Bakery website by producing a more user-friendly design, increasing user engagement, and simplifying the purchasing process.